Molecular engineering of ruthenium-based photosensitizers with superior photovoltaic performance in DSSCs: novel N-alkyl 2-phenylindole-based ancillary ligands. (20th January 2022) - Ashraf, Saba; Su, Rui; Akhtar, Javeed; Shuja, Ahmed; Siddiqi, Humaira M.; El-Shafei, Ahmed
Abstract : In this work, we report the design and successful synthesis of two new heteroleptic polypyridyl Ru(ii ) complexes (SD-5 and SD-6), by incorporating hetero-aromatic electron-donating N -alkyl-2-phenylindole moieties into the ancillary ligand. Abstract : In this work, we report the design and successful synthesis of two new heteroleptic polypyridyl Ru(ii ) complexes (SD-5 and SD-6), by incorporating hetero-aromatic electron-donating N -alkyl-2-phenylindole moieties into the ancillary ligand. These novel ruthenium complexes were used as photosensitizers for dye-sensitized solar cells. The primary objective was to investigate the electron-donating effect of the indole segments on the photo-related properties and the influence of the length of terminal alkyl chains tethered to N-indole on the charge recombination resistance. The chemical structures of both targeted compounds were confirmed via FT-IR, 1 H-NMR and mass spectrometry. Under the same device fabrication conditions, the photovoltaic performance of SD-6 outperformed that of SD-5 and N719 with an overall efficiency of 8.14% ( J SC = 19.21 mA cm −2, V OC = 0.675 V and FF = 62.7%), compared to 7.74% of N719 and 4.99% of SD-5 . The enhanced photovoltaic power of SD-6 can be attributed to the presence of long alkyl antennas (–C18 H37 ) in SD-6 ; it reduced the intermolecular aggregation of dyes and suppressed charge recombination, thus resulting in enhanced J SC and V OC values, respectively, compared to its analog SD-5 . Furthermore, the presence of indole moieties with long alkyl chains in the ancillary ligand enhanced the photovoltaic performance compared to N719 with bi-anchoring ligands. The photovoltaic and EIS measurements were consistent with the equilibrium molecular geometry calculated using density functional theory (DFT). The structure–property relationships have been discussed in detail.